An introduction to Mennonite history : a popular history of the Anabaptists and the Mennonites - Dyck, Cornelius J. (Herald Press, 1981)
A history of Anabaptist-Mennonite thought from the sixteenth century to the present, with a description of Mennonite life and thought around the world today.